2009
DOI: 10.1590/s1516-35982009000100023
|View full text |Cite
|
Sign up to set email alerts
|

Consumo, digestibilidade aparente dos nutrientes e comportamento ingestivo de bovinos da raça Holandesa alimentados com dietas contendo feno de capim-tifton 85 com diversos tamanhos de partícula

Abstract: RESUMO -Avaliaram-se o consumo, a digestibilidade aparente de nutrientes da dieta e o comportamento ingestivo de novilhos recebendo dietas contendo feno de capim-tifton 85 com diferentes tamanhos de partícula (5, 7, 10 mm e inteiro). Utilizaram-se quatro novilhos da raça Holandesa, castrados, com peso vivo médio de 300 kg e idade média de 20 meses, em delineamento quadrado latino 4 × 4, com quatro animais e quatro períodos. Os consumos de matéria seca, matéria orgânica, proteína bruta, extrato etéreo, fibra em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
(9 reference statements)
1
3
0
7
Order By: Relevance
“…Other correlations were also significant; rumination time with efficiency of dry matter rumination (r = -0.82) and neutral detergent fiber (r = -0.55), showing that the increase in rumination time negatively influenced the rumination efficiency. The results of the present study were in line with those presented in the literature (Bürger et al, 2000;Pereira et al, 2009;Missio et al, 2010) for the same animal category, where the authors reported variation from 4.23 to 8.96 hours/day, which was a reflection of the quantity of roughage used in the diets, the size of the roughage particle and the diet composition.…”
Section: Resultssupporting
confidence: 93%
“…Other correlations were also significant; rumination time with efficiency of dry matter rumination (r = -0.82) and neutral detergent fiber (r = -0.55), showing that the increase in rumination time negatively influenced the rumination efficiency. The results of the present study were in line with those presented in the literature (Bürger et al, 2000;Pereira et al, 2009;Missio et al, 2010) for the same animal category, where the authors reported variation from 4.23 to 8.96 hours/day, which was a reflection of the quantity of roughage used in the diets, the size of the roughage particle and the diet composition.…”
Section: Resultssupporting
confidence: 93%
“…The sum of periods 1 and 2 corresponded to the longer time spent on consumption (82.21% of total consumption), so the consumption was concentrated during the day. These observations were also registered by Pereira et al (2009), Dado and Allen (1995), and Macedo et al (2007), who obtained an average of 57% of time spent feeding adding the periods 1 and 2. Dado and Allen (1995) reported that DMI is increased after feeding, when feed is still fresh.…”
Section: Ingestive Behaviourmentioning
confidence: 65%
“…When feed reaches the digestive tract, the intake rate limits consumption, depending mainly on the physical, mechanical, and nutritional quality of the feed. Between meals, feed is processed by the animal at a rate dependent on the area of the digestive tract, the level of enzymatic activity, bacterial load, and feed quality, and this processing rate is often the primary factor limiting food intake (BROOM; FRASER, 2010;PEREIRA et al, 2009;VAN SOEST, 1994).…”
Section: Resultsmentioning
confidence: 99%